Comparison of serological and molecular panels for diagnosis of vector-borne diseases in dogs - Ricardo G Maggi; Adam J Birkenheuer; Barbara C Hegarty; Julie M Bradley; Michael G Levy; Edward B Breitschwerdt (Parasites & Vectors, 2014)
Abstract Background Canine vector-borne diseases (CVBD) are caused by a diverse array of pathogens with varying biological behaviors that result in a wide spectrum of clinical presentations and laboratory abnormalities. For many reasons, the diagnosis of canine vector-borne infectious diseases can be challenging for clinicians. The aim of the present study was to compare CVBD serological and molecular testing as the two most common methodologies used for screening healthy dogs or diagnosing sick dogs in which a vector-borne disease is suspected. Methods We used serological (Anaplasma species, Babesia canis, Bartonella henselae, Bartonella vinsonii subspecies berkhoffii, Borrelia burgdorferi, Ehrlichia canis, and SFG Rickettsia) and molecular assays to assess for exposure to, or infection with, 10 genera of organisms that cause CVBDs (Anaplasma, Babesia, Bartonella, Borrelia, Ehrlichia, Francisella, hemotropic Mycoplasma, Neorickettsia, Rickettsia, and Dirofilaria). Paired serum and EDTA blood samples from 30 clinically healthy dogs (Group I) and from 69 sick dogs suspected of having one or more canine vector-borne diseases (Groups II-IV), were tested in parallel to establish exposure to or infection with the specific CVBDs targeted in this study. Results Among all dogs tested (Groups I-IV), the molecular prevalences for individual CVBD pathogens ranged between 23.3 and 39.1%. Similarly, pathogen-specific seroprevalences ranged from 43.3% to 59.4% among healthy and sick dogs (Groups I-IV). Among these representative sample groupings, a panel combining serological and molecular assays run in parallel resulted in a 4-58% increase in the recognition of exposure to or infection with CVBD. Conclusions We conclude that serological and PCR assays should be used in parallel to maximize CVBD diagnosis.